Involvement of Teenage-Students in Cyberbullying on WhatsApp - Riyayanatasya, Yy Wima; Rahayu, Rahayu (JURNAL KOMUNIKASI INDONESIA, 2020)
Cyberbullying has become a crucial issue that continues to develop in line with the advancement of technology. This study is presented to show that cyberbullying can be analyzed through the perspective of communication science, particularly since cyberbullying can be found on the social media WhatsApp. This article aims to reveal the intensity of junior high school (sekolah menengah pertama – SMP) students’ involvement in cyberbullying via the social media WhatsApp, and their responses to being a victim of cyberbullying. The research employed a survey method by involving 281 randomly selected respondents from six SMPs in Yogyakarta Municipality. Data collection was carried out by using a questionnaire. The study found that all the students, who were respondents in the research, had been involved in at least one out of the seven types of cyberbullying, which are flaming, harassment, denigration, impersonation, outing and trickery, exclusion, and cyberstalking. The intensity of the student’s involvement varies and is identified to be in the low and moderate categories. Exclusion is the most common type of cyberbullying often experienced by the students, while impersonation is categorized as having the lowest intensity. In the study, more students in seventh grade were found to be victims of cyberbullying.